EKSISTENSI KOMUNITAS SKATEBOARD DI KOTA MANADO - Kolinug, Andree Aldy (HOLISTIK, Journal Of Social and Culture, 2017)
The existence of skateboarding in Indonesia was developed very fast, we cansee it from government’s support in every city to give the good facilities. But thatthings not happen in Manado City which has a lots of skateboard’s communitiesbut unfortunately there are no supporting facilities. This community has the mostimportant role in order to keeps the existence and the development ofskateboarding in Manado. This community also has a lots of factor to supportskateboarding’s development in Manado City. Therefore, the existance is animportant thing in order to keeps the community alive.The aim of this research is to know the using of this group to keeps theirexsitance, and also to know what kind of interference and supporting factor thatcommunity faced. This explorative qualitative research is using two data source,primary data and secondary data. Data collecting tech are using interview,observation, and documentation source. Master data source is using byinterviewing some senior’s member and junior’s member of Manado CitySkateboarding community, and with using participation observation.In order to keeps their existence, this community with unformal waydeciding and planning some element that can support. The next step isimplementation based on how to do their already plan. The working system of thisManado City Skateboarding community is flow with what they are to be withoutcaring for the formal vision and mission. On that implementation, this communityalso face some interference which come from inside or outside that they can solvebecause of the supporting factor from each member. Strategy that they use inorder to keeps their existence is pretty success. We can see it from the length ofthis community and also from the positive response that given from some personoutside the community.Keywords : community, skateboard, exsitance